1998
DOI: 10.1002/chin.199801168
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Binding Affinity of 2‐Phenylimidazo[1,2‐a]pyridine Derivatives for Both Central and Peripheral Benzodiazepine Receptors. A New Series of High‐Affinity and Selective Ligands for the Peripheral Type.

Abstract: Synthesis and Binding Affinity of 2-Phenylimidazo[1,2-a]pyridine Derivatives for Both Central and Peripheral Benzodiazepine Receptors. A New Series of High-Affinity and Selective Ligands for the Peripheral Type.-A series of title compounds, e.g. (I), is synthesized by methods similar to that described for amide (Ii). Amides (Ie)-(Ii) show high affinity and selectivity for peripheral benzodiazepine receptors and they stimulate production of neurosteroids.-(TRAPANI, G.; FRANCO, M.; RICCIARDI, L.; LATROFA, A.; GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Binding assays were performed according to the methods described previously. Briefly, male Sprague−Dawley CD rats at 30 days of age were killed, the brain was rapidly removed, the cerebral cortex was dissected, and all tissues were stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding assays were performed according to the methods described previously. Briefly, male Sprague−Dawley CD rats at 30 days of age were killed, the brain was rapidly removed, the cerebral cortex was dissected, and all tissues were stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In our recent paper we reported on a Pt complex with the ligand 2-[6,8-dichloro-2-(1,3-thiazol-2-yl)- H -imidazo[1,2- a ]pyridin-3-yl]- N , N -di- n -propylacetamide ( 1 , Figure ), which is endowed with high affinity and selectivity for TSPO and belongs to a series of potent and selective TSPO ligands containing the imidazopyridine nucleus. This molecule, 1 , characterized by a thiazole ring in position 2 of the imidazopyridine nucleus, demonstrated to act as a chelating agent toward platinum, so forming a large planar aromatic polycyclic system with potential intercalative properties toward DNA (a feature that could help to circumvent cisplatin resistance) . The obtained complex, cis -[PtCl 2 {2-[6,8-dichloro-2-(1,3-thiazol-2-yl)- H -imidazo[1,2- a ]pyridin-3-yl]- N , N -di- n -propylacetamide}] ( 2 , Figure ), combines the alkylating properties of the metal residue with the high affinity (in nanomolar concentration) and selectivity of 1 for TSPO-overexpressing tissues.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported a series of potent and selective PBR ligands, designed from Alpidem by introducing several substituents on the imidazopyridine nucleus (Compounds 5 , Chart ). Our structure−activity correlations revealed that substitution at the 8-position of the imidazopyridine nucleus is a key factor for improving affinity and selectivity toward peripheral binding sites. Substitutions at the 8-position with lipophilic groups and at the para position of the phenyl ring at C(2) with a chlorine atom are crucial for high affinity and selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…The increasing availability of PET, and the short half-life of carbon-11 has prompted the development of novel [ 18 F] ligands, including the N -benzyl- N -(2-phenoxyaryl)acetamides ,, and 2-(2-(4-tert-butylphenyl)-6-fluoroimidazo[1,2-b]pyridazin-3-yl)- N , N -diethylacetamide (PBR132), with promising preclinical data. Similarly, halogenated 2-phenylimidazopyridines, imidazopyridazines, and pyrazolopyrimidine-3-acetamides have been prepared with high affinity and selectivity for the PBR receptor. , One aspect of the extensive structure affinity studies carried out in our laboratory , and elsewhere has revealed that 6-chloro-2-phenylimidazo[1,2- a ]pyridine-3-yl acetamides (Figure ), where R 1 and R 2 are small alkyl groups, have high affinity for the PBR when the para-substituent X on the 2-phenyl ring is moderately large. Consequently, a large number of ligands based on this structure have been prepared bearing the SPECT isotope I-123.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, halogenated 2-phenylimidazopyridines, imidazopyridazines, and pyrazolopyrimidine-3-acetamides have been prepared with high affinity and selectivity for the PBR receptor. 24,29 One aspect of the extensive structure affinity studies carried out in our laboratory 24,29 and elsewhere 38 has revealed that 6-chloro-2-phenylimidazo[1,2-a]pyridine-3-yl acetamides (Figure 2), where R 1 and R 2 are small alkyl groups, have high affinity for the PBR when the para-substituent X on the 2-phenyl ring is moderately large. Consequently, a large number of ligands based on this structure have been prepared bearing the SPECT isotope I-123.…”
Section: Introductionmentioning
confidence: 96%